Pressure tide gauge records from the Atlantic shelf off Tierra del Fuego, southernmost South America - Richter, Andreas Jorg (2012)
Based on pressure tide gauge observations at three sites off the Atlantic coast of Tierra del Fuego main island, time series spanning one to seven months of bottom pressure and sea-level variations are derived and analysed to reveal the major driving mechanisms. Ocean tides account for 99.5% of the total energy of the sea-level variations. The amplitudes and phases of a comprehensive set of tidal constituents resulting from a harmonic tidal analysis are presented. Exceptionally large shallow-water tides are identified. The second largest contribution is due to the local inverse barometer model accounting for up to 65% of the variance of the tide residual sea-level variations. Close to the shore a significant topographic modulation of the sea-level variations is revealed. The in situ observations are compared with six recent global ocean tide models, official tide tables, and sea-surface heights derived from satellite altimetry data. The amplitudes and phases predicted by the ocean tide models for the semidiurnal and diurnal constituents agree with those derived from our tide gauge records on average within 2 cm and 51, respectively. In the time domain the tidal signal represented by the models deviates typically by a few decimetres from that extracted from our records. Absolute altimeter biases were determined for the Jason-2, Jason-1 extended mission, and Envisat satellite altimeters. Relative sea- level variations are represented by the altimetry data with an accuracy of the order of 5 cm.